Yuridis Review Peer to Peer Lending Syariah pada Layanan Google Play Store - Ubadillah, Asep; Asfari, Zulfikar (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
The development of financial technology (fintech) has enriched economic transactions by making them more practical and digital. Peer-to-peer lending (P2P) applications are one example that offers online facilitation for lenders and borrowers. Google Play Store provides various P2P applications, including Dana Syariah and Alami Funding Syariah, which are designed for Muslims who manage their finances according to Shariah principles. This research aims to understand the mechanisms of Shariah-based P2P applications, user reviews, and the advantages and disadvantages of these applications. The researcher uses a qualitative method with a descriptive comparative approach. The results show that Dana Syariah focuses on real estate, while Alami Funding Syariah focuses on financing small and medium enterprises (SMEs) in Indonesia. Both applications conduct financing processes using contracts that comply with the fatwa of the Indonesian Ulama Council. Dana Syariah and Alami Funding Syariah have advantages and disadvantages according to user perspectives. User reviews are diverse, ranging from difficulties in accessing the application to overly strict requirements. However, many users benefit from the applications, such as investing in real estate and SMEs, receiving high returns, and conducting Shariah-compliant financing processes.